Interleukin-37 is increased in adult-onset Still’s disease and associated with disease activity - Chi, Huihui; Liu, Dongzhou; Sun, Yue; Hu, Qiongyi; Liu, Honglei; Cheng, Xiaobing; Ye, Junna; Shi, Hui; Yin, Yufeng; Liu, Mengru; Wu, Xinyao; Zhou, Zhuochao; et al. (Arthritis research & therapy, 2018)
Interleukin (IL)-37 has been known to play an immunosuppressive role in various inflammatory disorders, but whether it participates in the regulation of pathogenesis of adult-onset Still's disease (AOSD) has not been investigated. In this study, we examined serum IL-37 levels and their clinical association with AOSD, and we explored the anti-inflammatory effects of IL-37 on peripheral blood mononuclear cells (PBMCs) from patients with AOSD. Blood samples were collected from 62 patients with AOSD and 50 healthy control subjects (HC). The serum IL-37 levels were determined using an enzyme-linked immunosorbent assay (ELISA). The correlations of serum IL-37 levels with disease activity, laboratory values, and inflammatory cytokines in AOSD were analyzed by Spearman's correlation test. The correlations between serum IL-37 levels and clinical manifestations were analyzed by Mann-Whitney U test. PBMCs from ten patients with AOSD were stimulated with recombinant human IL-37 protein, and expression levels of tumor necrosis factor (TNF)-α, IL-6, IL-10, IL-1β, and IL-18 were determined by qRT-PCR and ELISA. A significantly higher IL-37 protein level was observed in patients with AOSD than in HC. Serum IL-37 levels correlated with systemic score, laboratory values, IL-1β, IL-18, and IL-10 in patients with AOSD. The expression levels of IL-37 were closely related to the patients with AOSD who also had fever, skin rash, lymphadenopathy, splenomegaly, myalgia, and arthralgia. Moreover, the production of proinflammatory cytokines such as IL-6, IL-1β, TNF-α, and IL-18 in PBMCs from patients with AOSD was obviously attenuated after recombinant human IL-37 stimulation. Increased expression of IL-37 and its positive correlation with disease activity suggest its involvement in AOSD pathogenesis. More importantly, IL-37 inhibits the expression of proinflammatory cytokines in PBMCs from patients with AOSD, indicating the potential anti-inflammatory role of IL-37 in AOSD. Thus, IL-37 may be a novel disease activity biomarker and research target in AOSD.